Search for new physics in rare top decays: t ¯ t spin correlations and other observables - Kiers, Ken (2014)
In this paper we study new-physics contributions to the top-quark decay t → bbc. We search for ways of detecting such new physics via measurements at the LHC. As top quarks are mainly produced at the LHC in tt production via gluon fusion, we analyze the process gg → tt → bbc bℓν . We find six observables that can be used to reveal the presence of new physics in t → bbc. Three are invariant mass-squared distributions involving two of the final-state particles in the top decay, and three are angular correlations between the final-state quarks coming from the t decay and the ℓ − coming from the t decay. The angular correlations are related to the t t spin correlation.